Use of Chitosan and White Glutinous Rice Flour Quality of Chicken Meat Burger: Burger - Monica, Metha; Fitriani, Ana; Setyaji, Hajar (International Journal of Applied and Scientific Research, 2024)
This research aims to increase the economic value of chicken meat by diversifying processed products, such as burgers. The study focuses on finding the right concentration ratio between white glutinous rice flour and chitosan to produce high-quality chicken meat burgers. The research used factorial RAL and analyzed parameters such as pH, WHC, color, water content, protein content, fat content, micro-element content (calcium and phosphor), and reducing sugar. Results showed that the moisture content of chicken burgers using white sticky rice was lower, while chitosan had a lower water content. The color of burgers using white sticky rice was reddish and greenish, while chitosan had a lower reduction sugar. Ca content was also lower, while phosphorus levels were higher in chitosan burgers. The WHC ranged from 18.869 - 48.7573 for chitosan burgers and 25.023 - 41, 2855 for chitosan burgers.